Change of Shape, Size and Form Related to Traditional and New Materials in Atoni Buildings in Central Timor: A Comparison of the Region Near Nikiniki, Soe and Kefamenanu - Zamolyi, Ferenc (International Journal of Environment, Architecture, and Societies, 2022)
This article is the second part of the analysis of the author´s field research, which was conducted in Timor in May 2004 in Maubesi, and in June 2011 near Soe and Nikiniki and Kefamenanu. The paper focuses on the region of Central Timor, settled by the Atoni Meto people, who live in round houses built on the ground. The house form and materials utilised differ somewhat in the higher regions of Central Timor and the lower-lying Eastern parts of Central Timor. The aim of this article is to explore how such building materials are utilised and whether they are or can be integrated into local vernacular building traditions. New materials are often used to imitate the more traditional ones, often incorporating structural details from the older technology and traditional materials which are copied. In other cases, new materials lead to a change in the appearance and structure of vernacular buildings. New materials already influencing the building due to their different, new properties, and designs are devised to adapt to these changes, which in the end result in an altered building. It appears that the highland regions of Central Timor near Soe and Nikiniki use a more conservative house design while in the region around Kefamenanu modern materials are more present in vernacular architecture. The use of concrete and corrugated iron to build lopos (traditional granaries and community buildings) is striking and has produced a new version of the traditional lopo.